Mathematical Analysis of Two Strains Covid-19 Disease Using SEIR Model - Adetayo Samuel Eegunjobi; Oluwole Daniel MAKINDE (Directorate for Research and Community Services (LPPM) ITB, 2022)
The biggest public health problem facing the whole world today is the COVID-19 pandemic. From the time COVID-19 came into the limelight, people have been losing their loved ones and relatives as a direct result of this disease. Here, we present a six-compartment epidemiological model that is deterministic in nature for the emergence and spread of two strains of the COVID-19 disease in a given community, with quarantine and recovery due to treatment. Employing the stability theory of differential equations, the model was qualitatively analyzed. We derived the basic reproduction number for both strains and investigated the sensitivity index of the parameters. In addition to this, we probed the global stability of the disease-free equilibrium. The disease-free equilibrium was revealed to be globally stable, provided and the model exhibited forward bifurcation. A numerical simulation was performed, and pertinent results are displayed graphically and discussed.